1986
DOI: 10.1128/mcb.6.5.1729
|View full text |Cite
|
Sign up to set email alerts
|

p185, a product of the neu proto-oncogene, is a receptorlike protein associated with tyrosine kinase activity.

Abstract: The neu oncogene was originally identified in cell lines derived from rat neuroectodermal tumors. neu is related to but distinct from the c-erbB gene, which encodes the epidermal growth factor (EGF) receptor. neu encodes a protein, designated p185, that is serologically related to the EGF receptor. Identification of the normal homolog of p185 encoded by the neu proto-oncogene enabled us to compare the product of the neu proto-oncogene with the mutated version specified by the neu oncogene and with the EGF rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
165
1
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(171 citation statements)
references
References 67 publications
(64 reference statements)
4
165
1
1
Order By: Relevance
“…The ErbB2DIC protein was expressed in FR3T3 rat embryonic ®broblast cells transfected with MMTVErbB2DIC ( Figure 1b, lane 2) but not cells transfected with an empty vector ( Figure 1b, lane 1). ErbB2 is phosphorylated in response to EGF when coexpressed with EGFR (Stern et al, 1986;Stern and Kamps, 1988). To determine the e ects of ErbB2DIC expression on the transphosphorylation of ErbB2 in response to EGF, FR3T3 cell lines expressing ErbB2DIC or the MMTV vector alone were mock treated or treated with EGF.…”
Section: Expression and Dominant Negative Activity Of A Truncated Erbb2mentioning
confidence: 99%
See 3 more Smart Citations
“…The ErbB2DIC protein was expressed in FR3T3 rat embryonic ®broblast cells transfected with MMTVErbB2DIC ( Figure 1b, lane 2) but not cells transfected with an empty vector ( Figure 1b, lane 1). ErbB2 is phosphorylated in response to EGF when coexpressed with EGFR (Stern et al, 1986;Stern and Kamps, 1988). To determine the e ects of ErbB2DIC expression on the transphosphorylation of ErbB2 in response to EGF, FR3T3 cell lines expressing ErbB2DIC or the MMTV vector alone were mock treated or treated with EGF.…”
Section: Expression and Dominant Negative Activity Of A Truncated Erbb2mentioning
confidence: 99%
“…Stable cell clones in 60 mm dishes were metabolically labeled, in the presence of 1 mM dexamethasone, by incubating for 16 h with 100 mCi of 35 Smethionine/cysteine in vitro cell labeling mix (Amersham). Labeled cells were lysed on ice in RIPA bu er (10 mM Tris, pH 7.4, 150 mM NaCl, 1% deoxycholate, 1% NP-40, 0.1% sodium dodecyl sulfate, with 1 mM phenylmethylsulfonyl uoride, and 1% aprotinin) and immunoprecipitations were performed by adding 1 mg of anti-c-neu Ab-4 (Oncogene Science) and 50 ml of preswollen protein A sepharose (Pharmacia) (Stern et al, 1986). Precipitated proteins were resolved by SDS ± PAGE on a 12% acrylamide gel and the resolving gel was processed in Opti¯uor (National Diagnostics) according to the manufacturer's instructions.…”
Section: Immunoprecipitation and Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The HRG-induced increase in serine phosphorylation of paxillin and cell scattering were selectively inhibited by a speci®c inhibitor of p38 MAPK or a dominant-negative p38 MAPK mutant, but not byIntroduction Abnormalities in the expression, structure, or activity of proto-oncogene products contribute to the development and maintenance of the malignant phenotype. For example, HER2 (also known as c-erbB2 or c-neu) encodes a 185 kD transmembrane glycoprotein with intrinsic tyrosine kinase activity (Stern et al, 1986) that has been shown to be overexpressed or ampli®ed, or both, in a number of human malignancies, including breast cancer (Slamon et al, 1987). Overexpression of the HER2 receptor is associated with increased progression and metastasis, an aggressive clinical course, and decreased disease-free survival in human breast cancer patients (Slamon et al, 1989).…”
mentioning
confidence: 99%